Adverse Effects of Metformin From Diabetes to COVID-19, Cancer, Neurodegenerative Diseases, and Aging: Is VDAC1 a Common Target? - Shoshan-Barmatz, Varda; Anand, Uttpal; Nahon-Crystal, Edna; Di Carlo, Marta; Shteinfer-Kuzmine, Anna (Frontiers in Physiology, 2021)
Abstract: Metformin has been used for treating diabetes mellitus since the late 1950s. In addition to its antihyperglycemic activity, it was shown to be a potential drug candidate for treating a range of other diseases that include various cancers, cardiovascular diseases, diabetic kidney disease, neurodegenerative diseases, renal diseases, obesity, inflammation, COVID-19 in diabetic patients, and aging. In this review, we focus on the important aspects of mitochondrial dysfunction in energy metabolism and cell death with their gatekeeper VDAC1 (voltage-dependent anion channel) as a possible metformin target, and summarize metformin’s effects in several diseases and gut microbiota. We question how the same drug can act on diseases with opposite characteristics, such as increasing apoptotic cell death in cancer, while inhibiting it in neurodegenerative diseases. Interestingly, metformin’s adverse effects in many diseases all show VDAC1 involvement, suggesting that it is a common factor in metformin-affecting diseases. The findings that metformin has an opposite effect on various diseases are consistent with the fact that VDAC 1 controls cell life and death, supporting the idea that it is a target for metformin.